Armenian Christians and Turkish Muslims: prospects for reconciliation through interfaith dialogue on the events of history - Van Gorder, A. Christian (Islam and Christian-Muslim relations, 2006)
In 1915, entire Armenian villages were burnt to the ground, residents being evacuated, murdered, or sent on forced death-marches. Armenian sources claim that as many as two million Armenians were murdered. These questions live on in present-day Muslim and Christian interaction. What should our response be to this relationship between past and present? This article explore how these unresolved histories affect present-day Muslim Turks and Christian Armenians in their faith and identity development. It considers the prospect of improved Turkish–Armenian relations as they relate to history and the role that religion might play in fostering reconciliation. Lastly, it suggests how these events might be instructive to Muslims, Christians, and Jews committed to interfaith partnerships for human rights.